The effect of education based on interactive augmented reality technology on students' creativity and problem solving - Rahim Moradi; Roghayeh Mohammadi (مطالعات روانشناسی تربیتی)
The aim was to investigate the effectiveness of interactive augmented reality technology on creativity and problem solving of sixth grade students. The current research method was a semi-experimental type and a pre-test-post-test design with a control group. The statistical population of this research included all the male students of the 6th grade of the elementary school in the 1st district of Karaj in the academic year 2022-2023. Available sampling method was used to select the statistical sample. In this way, 70 people were selected from among them and randomly replaced in two experimental (35 people) and control (35 people) groups. Data collection tools included creative thinking questionnaire and Heppner problem solving questionnaire. The experimental group was trained for 8 sessions of 45 minutes (2 sessions per week) with the augmented reality-based training protocol for the science lesson. The group was trained in the traditional and common way. After the end of the sessions in the experimental and control groups, the creativity and problem-solving questionnaire test was again implemented as a post-test on both groups and after collecting the data was analyzed. Descriptive and inferential statistics from SPSS statistical software were used for data analysis. The result of the research showed that interactive augmented reality is effective on the creativity of secondary school students. Also, the result of the research showed that interactive augmented reality is effective on problem solving ability and its sub-components, including scales of confidence in solving problems,